Hierarchical molybdenum-doped NiCoP@carbon microspheres: a highly-efficient electrocatalyst for the hydrogen evolution reaction. Issue 77 (6th September 2021) - Liu, Changhai; Yao, Yanhua; Sun, Lei; Luo, Linlin; Wang, Wenchang; Chen, Zhidong
Abstract : Hierarchical Mo-doped NiCoP@carbon (MNiCoP@C) hollow microspheres are designed and prepared via hydrothermal synthesis and subsequent thermal treatment. Abstract : Herein, we present hierarchical Mo-doped NiCoP@carbon microspheres that exhibit a noticeable enhancement in catalytic activity and fast kinetics for hydrogen evolution. An overpotential of 74.6 mV at 10 mA cm −2 and 54.9 mV dec −1 can be achieved. These results demonstrated the excellent electrochemical properties arising from the intrinsic characteristics of elemental doping and morphology control. We believe that this work opens a new avenue to fabricating TMD-based catalysts via the engineering of transition metal compounds.